UV-induced association of the CSB remodeling protein with chromatin requires ATP-dependent relief of N-terminal autorepression - Lake, Robert J. (2010)
The ATP-dependent chromatin remodeler CSB is essential for transcription-coupled DNA repair, and mutations in CSB lead to Cockayne syndrome. Here we examined the recruitment of CSB to chromatin after UV irradiation and uncovered a regulatory mechanism that ensures the specific association of this remodeler with chromatin. We demonstrate that ATP hydrolysis by CSB is essential for stable CSB-chromatin association after UV irradiation, and that defects in this association underlie some forms of Cockayne syndrome. We also show that the N-terminal region of CSB negatively regulates chromatin association during normal cell growth. Interestingly, in the absence of the negative-regulatory region, ATP hydrolysis becomes dispensable for chromatin association, indicating that CSB uses energy from ATP hydrolysis to overcome the inhibitory effect imposed by its N-terminal region. Together, our results suggest that the recruitment of CSB to lesion-stalled transcription is an ATP-dependent process and involves a gross conformational change of CSB.